2014
DOI: 10.1007/s00423-014-1249-8
|View full text |Cite
|
Sign up to set email alerts
|

Is clipping the preferable technique to perform sympathicotomy? A retrospective study and review of the literature

Abstract: Depending on the symptoms of the patient, different levels of the sympathetic chain should be addressed. When a higher rib level such as R2 is approached, which more likely will result in moderate to severe compensatory sweating, clipping should be preferred as it seems that this technique has indeed a potential for reversibility. As demonstrated, this method is at least as effective as an irreversible transection of the sympathetic chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In line with this finding, Liu et al compared R3 sympathicotomy an R4 sympathicotomy and found that interruption of the sympathetic chain at R4 does not compromise the therapeutic effect any more than interruption of sympathetic chain at R3 (8). Kocher et al reported that clipping is as effective as transection of the sympathetic chain in the treatment of hyperhidrosis (13). Based on our data, R4 sympathicotomy and R4 sympathetic clipping yielded better results for CS and patient satisfaction when compared to R3 sympathetic clipping.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In line with this finding, Liu et al compared R3 sympathicotomy an R4 sympathicotomy and found that interruption of the sympathetic chain at R4 does not compromise the therapeutic effect any more than interruption of sympathetic chain at R3 (8). Kocher et al reported that clipping is as effective as transection of the sympathetic chain in the treatment of hyperhidrosis (13). Based on our data, R4 sympathicotomy and R4 sympathetic clipping yielded better results for CS and patient satisfaction when compared to R3 sympathetic clipping.…”
Section: Discussionsupporting
confidence: 57%
“…Thoracoscopic sympathetic surgery is thus regarded as a definitive treatment for palmar hyperhidrosis. Indeed, thoracoscopic sympathetic surgery has lower complication rates irrespective of the method used to interrupt the sympathetic trunk; to date, however, the optimal surgical technique and level of sympathetic trunk interruption in thoracoscopic sympathetic surgery is still debated (5,13). We compared the clinical results by level and type of sympathetic disconnection in patients with palmar hyperhidrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common and the worst secondary effect of sympathectomy is compensatory sweating mainly involving back, abdomen, and lower limbs. 2 The clipping technique has multiple advantages as It can be performed safely and efficiently. Although clipping is as effective as any other sympathectomy method, but it is potentially reversible if the patient develops severe compensatory sweating.…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, there is no consensus on the technique to be applied, as cutting, cauterization, or clipping the sympathetic chain or ganglion can yield similar results with regard to the success of the procedure, patient satisfaction, and side effects. [5][6][7][8] The standard intervention is to cut the sympathetic chain by entering from the axilla through two or three ports. Recently, approaches through a transumbilical [9] or trans-areolar incision using a flexible endoscope have been reported for less scar and pain.…”
mentioning
confidence: 99%